Life Cycle Assessment (LCA) Analysis Of Concrete Slab Construction For Estimating The Environmental Impact - Annisa Nur Rakhmawati; Yatnanta Padma Devia; Indradi Wijatmiko (Rekayasa Sipil, 2020)
Global warming and air pollution become one of the environmental issues facing the world. the construction sector consumes about 40% of total global energy. Many strategies have been adopted to improve the efficiency of building construction to reduce material consumption and carbon emissions. One way to find out the environmental impact and carbon emissions produced is with a Life Cycle Assessment (LCA). This study aims to predict the environmental impact of concrete slab construction in two-story dwellings using the Life Cycle Assessment (LCA) approach of the material used with the help of software, namely Simapro 9.0. The scope of the study is the cradle to the grave. The results of the SimaPro 9.0 concrete plate construction analysis, especially in global warming are 1.02, E+07 kg CO2 eq. The biggest contribution to the manufacture of concrete slabs is the casting process with a value of 1.00, E+07 kg CO2 eq.